2014
DOI: 10.1177/0013161x13514440
|View full text |Cite
|
Sign up to set email alerts
|

Social Justice Leadership and Inclusion

Abstract: Research Approach: This cross case study describes the challenges that two principals working in one urban school district addressed while attempting to transform their school cultures to embrace an inclusion model. Analysis of interviews and observations in each school revealed the actions, values, and orientations of the individual leaders and the influences of conflicts and dilemmas that exist in social justice work. Findings: The article describes how two principals enacted social justice leadership by mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(52 citation statements)
references
References 41 publications
1
47
0
4
Order By: Relevance
“…While the literature on superintendent leadership generally underscores the importance of the superintendent as a "democratic-political leader" skilled at engaging in community and state politics (Kowalski, 2001;Kowalski et al, 2010;Kowalski & Björk, 2005), few empirical studies have identified specific instances where superintendent's successfully influenced statewide policy in the name of a social justice reform. This finding is also important as it relates to scholarship focused on social justice leadership, which often emphasizes the importance of consciousness and recognition of injustices, but overlooks many of the structural and technical challenges to educational leadership that can cripple any equity-oriented reform before it gets off the ground (DeMatthews, 2016;DeMatthews & Mawhinney, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature on superintendent leadership generally underscores the importance of the superintendent as a "democratic-political leader" skilled at engaging in community and state politics (Kowalski, 2001;Kowalski et al, 2010;Kowalski & Björk, 2005), few empirical studies have identified specific instances where superintendent's successfully influenced statewide policy in the name of a social justice reform. This finding is also important as it relates to scholarship focused on social justice leadership, which often emphasizes the importance of consciousness and recognition of injustices, but overlooks many of the structural and technical challenges to educational leadership that can cripple any equity-oriented reform before it gets off the ground (DeMatthews, 2016;DeMatthews & Mawhinney, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the internal and external challenges as well as the social justice dilemmas confronted by principals in schools (DeMatthews, 2016;DeMatthews & Mawhinney, 2014) is also germane to understanding social justice leadership for the superintendent. Unpacking the complexity of social justice further elucidates its applicability and pertinence to superintendents.…”
Section: Superintendents As Social Justice Leadersmentioning
confidence: 99%
“…Effecting such a change from generic to social justice leadership involves many challenges, which might even be paralyzing for principals (DeMatthews & Mawhinney, 2014). Principals have also been found to compromise on some of their religious obligations for social justice, which Marshall and Oliva (2010, p. 143)…”
Section: Challenging Timesmentioning
confidence: 99%
“…Bruce (2013, p. 608) urges leaders to work against the 'damaging cultural cycle of hostility and invisibility' for LGBT persons. Social justice leaders who recognize policies and systems that perpetuate inequalities, take action (DeMatthews & Mawhinney, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%